An uncommon cause of recurrent presyncope, dizziness, and tachycardia: a case report of diffuse, adult-onset Nesidioblastosis/Non-Insulinoma Pancreatogenous Hypoglycemia Syndrome (NIPHS) - Dieterle, Martin P.; Husari, Ayman; Prozmann, Sophie Nicole; Wiethoff, Hendrik; Stenzinger, Albrecht; Röhrich, Manuel; Pfeiffer, Uwe; Kießling, Wolfgang Rüdiger; Engel, Helena; Sourij, Harald; Steinberg, Thorsten; Tomakidi, Pascal; et al. (Biomedicines, 2023)
Neurovegetative and autonomic symptoms are common presentations of various diseases, ranging from psychosomatic to severe organic disorders. A 23-year-old man presented with a history of recurrent presyncope, dizziness, and tachycardia. Repeated diagnostic work-up in various clinical settings could not identify any definite cause for approximately eight years. However, the incidental detection of postprandial and exercise-induced hypoglycemia was suggestive of an insulin-related disorder. A 72 h plasma glucose fasting test revealed endogenous hyperinsulinism. Upon imaging studies, no tumor mass potentially indicating insulinoma could be detected. 68Ga-DOTA-Exendin-4 PET/CT showed diffuse tracer enrichment throughout the whole pancreas. A subtotal pancreatectomy was performed, and the diagnosis of diffuse, adult-onset nesidioblastosis was established histopathologically. This corresponds to the clinical findings of a functional β-cell disorder, also known as non-insulinoma pancreatogenous hypoglycemia syndrome (NIPHS). After nine months, the symptoms recurred, making complete pancreatectomy necessary. Postoperative laboratory evaluation exhibited no residual endogenous C-peptide production. This case illustrates the diagnostic challenges in patients presenting with unspecific, neurovegetative and autonomic symptoms with a severe and rare underlying cause.
Veröffentlicht: 17. Juni 2023
Gesehen am 14.08.2023